Vitamin K Deficiency Presenting in an Infant with an Anterior Mediastinal Mass: A Case Report and Review of the Literature - Palau, Mauricio A. (Case Rep Pediatr, 2017)
We report a case of a 1-month-old infant with spontaneous thymic hemorrhage secondary to severe vitamin K deficiency. He was brought to medical attention due to scrotal bruising and during evaluation was noted to be tachypneic and hypoxemic. Chest X-ray revealed an enlarged cardiothymic silhouette, and a follow-up echocardiogram revealed a mass in the anterior mediastinum. Routine laboratory work-up revealed severe coagulopathy. Further questioning revealed the patient had not received prophylactic vitamin K at birth. The coagulopathy resolved with administration of vitamin K, and a biopsy confirmed the anterior mediastinal mass was due to spontaneous thymic hemorrhage.